If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 5r = 10 + -1r Add '-10' to each side of the equation. 10 + -10 + 5r = 10 + -10 + -1r Combine like terms: 10 + -10 = 0 0 + 5r = 10 + -10 + -1r 5r = 10 + -10 + -1r Combine like terms: 10 + -10 = 0 5r = 0 + -1r 5r = -1r Solving 5r = -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. 5r + r = -1r + r Combine like terms: 5r + r = 6r 6r = -1r + r Combine like terms: -1r + r = 0 6r = 0 Divide each side by '6'. r = 0 Simplifying r = 0
| (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) | | 4+5-2=33 | | -2y+6+9y= | | 2/3-1/x=5/3x | | 3(n-4)=-15 | | X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= | | X^2+x+1=2 | | 8x+2z=4+7y | | 5x+2.5y=840 | | 7p-10=-3p+5 | | 10p+5=5p-5 | | 12y+8=13y-18 | | 20-2x=x+8 | | x^2-10=350 | | 17=9y-5y-3 | | yl=14j+3k | | 11=-9x+5x | | 324÷1/8 | | 16N=2(N+12)+2N | | 5x+5=6y | | 7(x-9)=14 | | 2x+(5x-3y)= | | 16N=(N+12)+2N | | -1.8=.4x | | 3x+1=9x+7 | | -xln(4)+xln(8)=ln(3) | | 15s^3+35s^2+18s=-2s |